Cigarette smoking & Malaria: Frequency of Malaria in Smokers versus Non Smokers. - Ghulam Mustafa Jamalil, Masood Noor Nabi Dahri2, Safdar Ali jamali3, Awais Bashir Larik4, Shazia Jamali5, Farzana Memon6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
BACKGROUND: Frequency of malaria is has been changed in region according to environmental factor and diseases. Smoking is generally injurious to health, is it protective from malaria or not yet not established. OBJECTIVE: DESIGN: This was a cross sectional study. SETTING: research was conducted at department of medicine, Peoples medical University Hospital Nawabshah from March 2018 to February 2019. SAMPLE SIZE: 221 patients male and females’ genders with malaria were selected who fulfilled criterion was included. MATERIAL AND METHODS: after selection the subjects were categorized for variable analyses like age, gender, malarial features, duration of malaria and presence of malaria parasite and smoker status of patient. Clinical examination was carried out for malaria diagnosis. Samples of blood for malaria parasite and blood grouping were collected. RESULTS: There were 112 (50.79r) males and 109 (49.39r) females. 167(75.6%) were not smokers and 54(24.4%) were smokers. Plasmodium vivax was positive in131 (59.3%) cases and plasmodium falciparum 90(40.7%). there were 91 (41.2%) were from urban areas, while 130(58.6%) from rural setup. Smoking grouping was done and different groups like smokers versus non smokers were analyzed for malaria parasite positive. CONCLUSION: There is no relationship of cigarette smoking as a preventive tool of malaria; our study concludes that malaria is common in non smokers as compared to smokers.